Pemanfaatan Pati Kentang dan Selulosa Batang Jerami Padi sebagai Bahan Baku Pembuatan Bioplastik yang Ramah Lingkungan - Mutia Fadilah Nasution; Abdul Halim Daulay; Ridwan Yusuf Lubis (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to overcome the weaknesses of starch-based bioplastics by utilizing cellulose extracted from rice straw stalks. The increasing amount of conventional plastic waste that is difficult to decompose has created an urgent environmental problem, so that bioplastics have emerged as an environmentally friendly alternative. However, bioplastics from potato starch have low water resistance and less than optimal mechanical properties. Rice straw stalks were chosen because of their abundant availability and high cellulose content (32-47%). The process of making bioplastics was carried out with variations in the composition of potato starch and rice straw stalk cellulose (100%: 0%; 87.5%: 12.5%; 75%: 25%; and 62.5%: 37.5%), with the addition of chitosan (2 g) and glycerol (2 ml) as additives. The characterizations conducted included water absorption test (ASTM D570-98), biodegradation test, tensile strength test (ASTM E8M), percent elongation (ASTM D882-12), and identification of functional groups using FTIR (Fourier Transform Infrared). The results showed that the addition of rice straw cellulose had a positive effect on the characteristics of bioplastics. The best water absorption test was obtained in sample C (75% Starch: 25% Cellulose) with a value of 13% which meets the ASTM D570-98 standard. The best biodegradation test was obtained in sample B (87.5% Starch: 12.5% ​​Cellulose) with a value of 62%. The maximum tensile strength value was recorded at 1.23 MPa in sample C, and the maximum percent elongation value was 99.2% in sample D. FTIR analysis confirmed the presence of main functional groups (O-H, C-H, N-H, C-O) which indicated an effective interaction between potato starch, rice straw cellulose, and chitosan. Overall, this composite bioplastic shows optimal potential and characteristics as an environmentally friendly material.